A nucleosomal surface defines an integration hotspot for the Saccharomyces cerevisiae Ty1 retrotransposon - Baller, Joshua A.; Gao, Jiquan; Stamenova, Radostina; Curcio, M. Joan; Voytas, Daniel F. (Genome Research, 2012)
Ty1, the most abundant retrotransposon in Saccharomyces cerevisiae, integrates preferentially upstream of genes transcribed by RNA polymerase III (Pol III). Targeting is likely due to interactions between the Ty1 integration complex and a feature of chromatin characteristic of sites of Pol III transcription. To better understand Ty1 targeting determinants, >150,000 Ty1 insertions were mapped onto the S. cerevisiae genome sequence. Logistic regression was used to assess relationships between patterns of Ty1 integration and various genomic features, including genome-wide data sets of histone modifications and transcription-factor binding sites. Nucleosomes were positively associated with Ty1 insertions, and fine-scale mapping of insertions upstream of genes transcribed by Pol III indicated that Ty1 preferentially integrates into nucleosome-bound DNA near the H2A/H2B interface. Outside of genes transcribed by Pol III, Ty1 avoids coding sequences, a pattern that is not due to selection, but rather reflects a preference for nucleosome-rich sites flanking genes. Ty1 insertion sites were also mapped in four mutant lines that affect Ty1 transposition frequency or integration specificity (rrm3Δ, hos2Δ, rtt109Δ, and rad6Δ). Patterns of integration were largely preserved in the mutants, although significantly more insertions into coding sequences were observed in the rad6Δ strain, suggesting a loosening of target specificity in this mutant that lacks an enzyme involved in ubiquitinating H2A. Overall, our data suggest that nucleosomes are necessary for Ty1 integration, and that a secondary factor, likely a histone modification or nucleosome-bound factor enriched at sites of Pol III transcription, determines preferred target sites.
10.1101/gr.129585.111